NEW PROPOSALS FOR THE „FBIH RED LIST OF PLANTS“ - Hasanbegović, Anis (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
After five years of field research across Federation of Bosnia and Herzegovina, as well as studying numerous botanical publications, especially ones considering plant protection, it has been established that some plant species should be listed in “Red list of FB&H”, with the accent on Euphorbia peplus, Seseli rigidum and Sesleria ujchelyii.Temporary and final IUCN status have been recommended for each plant species. Final status should be assigned after chronological and phytocoenological investigation. Plant material from National Museum BiH-SARA has been used for this research. For Euphorbia peplus and Sesleria ujchelyii no herbarium specimen has been found. These species were not part of “List of plant species (Pteridophyte and Spermatophyte) for Red book of Bosnia and Herzegovina”.